Born with Wings: The Spiritual Journey of a Modern Muslim Woman - Daisy Khan (Random House Audio, 2018)
Raised in a progressive Muslim family in the shadows of the Himalayan mountains, where she attended a Catholic girls' school, Daisy experienced culture shock when her family sent her to the States to attend high school in a mostly Jewish Long Island suburb. Ambitious and talented, she quickly climbed the corporate ladder after college as an architectural designer in New York City. Though she loved the freedom that came with being a career woman, she felt that something was missing from her life.